Healthspan Improvements in Caenorhabditis elegans with Traditional Chinese Herbal Tea. (16th December 2020) - Lin, Chunxiu; Zhang, Xiaoying; Zhuang, Chuting; Lin, Yugui; Cao, Yong; Chen, Yunjiao
Abstract : Searching for natural and safe herbal tea with health benefits has attracted more and more attention, which is of great significance for reducing disease risk. A Chinese traditional herbal tea (HT) is rich in active ingredients extracted from natural plants. Numerous pharmacological studies showed that HT had the potential to improve health, including antidepression and antioxidant effects. In this study, we proposed a strategy to explore the role and underlying mechanism of HT in improving healthspan of a Caenorhabditis elegans model. First, we found that HT significantly prolonged the lifespan without reducing fertility in worms. Second, stress resistance (oxidative stress and heat stress) was enhanced and A β - and polyQ-induced toxicity was relieved significantly by HT treatment. Both fat deposition and age pigment accumulation were found to be significantly reduced in HT-treated worms. The locomotion in mid-late stages was improved, indicating that behavioral mobility was also significantly enhanced. Furthermore, the main components of HT were eighteen polyphenols and two terpenoids. Finally, it was found that this protective mechanism was positively correlated with the insulin/insulin-like growth factor signaling- (IIS-) dependent manner, which went through promoting the nuclear localization of DAF-16 and its downstream SOD-3 expression. These results suggested that HT had an important role in improving health, which might serve as a promising healthy tea.